A study on the Current Situation and Countermeasures of Green Travel for College Students. Issue 1 (July 2020) - Yuan, Yifu; Zhang, Qiuping; Mao, An; Luo, Yujie
Abstract: With the rapid development of urbanization, a number of problems such as traffic congestion and air pollution are becoming more and more serious. Green travel is an important part of urban planning, which can effectively alleviate environmental pollution. As an important part of urban population, college students have distinct characteristics in travel demand, travel mode, and other aspects. Their cognition of green travel also has a tremendous impact on urban traffic planning and development. Taking Shandong Agricultural University as a case study, this study investigated the green travel situation of college students in the form of questionnaire, and analyzed their travel characteristics and influencing factors. Most people think that when dealing with the traffic problems, the government should play a major role and put forward rectification measures; in the existing green travel mode, the use frequency of bicycles or electric vehicles is not very high, and there are many problems in the use process; for short-distance travel, many people use walking or co-riding, etc. After analyzing the relevant factors, this study proposed targeted measures to encourage and guide students to choose green travel.